A Special Type of Pseudonym: Postmodern Apocrypha in Contemporary Hungarian Literature - Németh, Zoltán (Anafora, 2024)
The subject of this paper is a particular type of literary pseudonym, the postmodern apocryphal pseudonym, which uses the name of a classical author and is exposed already at the moment of publication. The paper addresses the theoretical issues of authorship, the problematic of the author’s name, and also discusses the most important works of postmodern Hungarian literature with pseudonyms. The analysis of the works that can be classified as playful postmodern apocrypha leads to the conclusion that the type of pseudonym has a decisive influence on interpretation, and that it is, therefore, essential to distinguish the specific ways in which pseudonyms are used in the texts.